2008
DOI: 10.1136/bjsm.2008.051565
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of football (soccer) injuries in Benin City, Nigeria

Abstract: A prevalence rate of 81.6% was recorded. Sprain was the leading injury type, while the ankle was the most affected anatomical site. Factors such as weather, previous injury, experience, role, and activity tend to influence injury occurrence. Soccer injury also has economic, physical and psychological implications. It is therefore recommended that preventive measures such as adequate treatment of injuries, full rehabilitation after injuries, use of protective equipment, appropriate exercises and warm-ups, conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
43
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 25 publications
9
43
0
4
Order By: Relevance
“…midfielders and defenders, were more prone to injury than players in other positions on the field. The correlation between a player's position and the occurrence of injuries is supported by findings reported in the literature, stating that players in contact positions, such as defenders, 2,6 were more prone to injury.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…midfielders and defenders, were more prone to injury than players in other positions on the field. The correlation between a player's position and the occurrence of injuries is supported by findings reported in the literature, stating that players in contact positions, such as defenders, 2,6 were more prone to injury.…”
Section: Discussionsupporting
confidence: 61%
“…2,7,8 An injury rate of 2.9 per 1 000 hours of practice, as opposed to 35.3 per 1 000 hours of match play, was noted by Morgan and Oberlander. 7 In a study of the epidemiology of soccer injuries conducted in Nigeria, 2 it was found that strikers and defenders were most commonly injured, especially those playing in amateur leagues.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Recent European (Dauty & Collon, 2011;Ekstrand, Hagglund, & Walden, 2011b;Hagglund, Walden, & Ekstrand, 2005) and American (Morgan & Oberlander, 2001) epidemiological studies of professional male football players reported an overall incidence of approximately 6-8 injuries per 1000 h of exposure. Previous studies have shown that football injuries mainly affected the lower extremities (Wong & Hong, 2005), particularly the ankle, knee or thigh (Azubuike & Okojie, 2009;Ekstrand, Hagglund, & Walden, 2011a;Junge & Dvorak, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[19] However, another study on African players showed that defenders sustained the most injuries over a full season, followed by forwards, midfielders and goalkeepers. [20] In this study, 24% of all injuries sustained over a season were owing to unfair play. Inconsistent refereeing during the season may compound this.…”
Section: Discussionmentioning
confidence: 99%